IDEOLOGI PATRIARKI PADA NOVEL RONGGENG DUKUH PARUK KARYA AHMAD TOHARI - * Sudarwati (Universitas 17 Agustus 1945 Surabaya, 2011)
Abstrak. Ronggeng Dukuh Paruk, a novel written by Ahmad Tohari, described the experience of life under a patriarchal culture. The approach of he study was the sociology of literature, especially feminist criticism and Gramsci’s theory of hegemony. There are five points that can be drawn from the analysis. First, despite her physical image of beauty, Srintil was uneducated and unmarried woman. From mental imagery aspects: she was so naive or stupid and was not aware of the role of her position. From socio-economic and cultural image: she was from the lower rank society so that she was unable to demand her emancipation. Second, Srintil’s body was used as a commodity. Her life was defined by men. The decision to be a ronggeng dancer was determined by men (Sakarya and the partner of ronggeng shaman). Being a ronggeng dancer, she was still controlled by men (Sakarya, partner of the ronggeng and the sex lovers). Her income was also enjoyed by men (shaman partner, calung drummer). Third, Srintil was appointed a ronggeng dancer because of her beauty, her skill of dancing, and her willingness to have sex with any men as far as they agreed with the payment. Her existence was protected by the society and had become the identity of Paruk village. Fourth, Srintil had verbally been abused sexually and socially. Fifth, Srintil’s grandfather, successfully made Srintil willingly become a ronggeng dancer in the name of cultural conservation. Kertareja, Srintil’s partner, successfully exploited Srintil’s body with the powers for his personal gain. Srintil did not realize that she was constantly used as an object.Kata kunci: ideologi patriarki, hegemoni, kritik feminism, eksploitasi tubuh